Matters of engagement
1 online resource.
Keywords: "By drawing on a broad range of disciplinary and cross-disciplinary expertise, this study addresses the history of emotions in relation to cross-cultural movement, exchange, contact, and changing connections in the later medieval and early modern periods. The essays cover a wide range of thematic and disciplinary areas and are organised around the primary sources on which they are based. The discussion of emotions in a wide range of sources including letters, images, material culture, travel writing, and literary accounts makes Matters of Engagement an invaluable source for both scholars and students concerned with the history of premodern emotions"--